2014
DOI: 10.1371/journal.pone.0091116
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Common Preleukemic Gene Fusions in Umbilical Cord Blood in Slovak Population

Abstract: The first event in origination of many childhood leukemias is likely the presence of preleukemic clone (transformed hematopoietic stem/progenitor cells with preleukemic gene fusions (PGF)) in newborn. Thus, the screening of umbilical cord blood (UCB) for PGF may be of high importance for developing strategies for childhood leukemia prevention and treatment. However, the data on incidence of PGF in UCB are contradictive. We have compared multiplex polymerase chain reaction (PCR) and real-time quantitative PCR (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
51
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 40 publications
10
51
1
1
Order By: Relevance
“…The quantitative analysis of summary data confirmed the tendency observed in the first 200 samples, namely an extremely low level of studied PFG in few positive samples, reaching usually < 6 copies per 100,000 cells. Our data clearly show that the amount of PFG in the majority of PFG + UCB samples is very close to the threshold of RT-qPCR sensitivity, which was reached at approximately 1–3 copies per 100,000 cells in our hands [14]. This fact stresses the sensitivity limitations of the screening method and suggests that only an approximate estimation of PFG incidence can be made if the obtained data are only slightly above the sensitivity level.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The quantitative analysis of summary data confirmed the tendency observed in the first 200 samples, namely an extremely low level of studied PFG in few positive samples, reaching usually < 6 copies per 100,000 cells. Our data clearly show that the amount of PFG in the majority of PFG + UCB samples is very close to the threshold of RT-qPCR sensitivity, which was reached at approximately 1–3 copies per 100,000 cells in our hands [14]. This fact stresses the sensitivity limitations of the screening method and suggests that only an approximate estimation of PFG incidence can be made if the obtained data are only slightly above the sensitivity level.…”
Section: Discussionsupporting
confidence: 72%
“…In their pioneer study, the Greaves’ group reported ~1.06% incidence of TEL-AML1/ETV6-RUNX1, the most common ALL-associated PFG, in umbilical cord blood (UCB) samples from England and Italy [10]. These data were further confirmed by other groups by screening UCB of newborns from Czech Republic, Japan, USA, and Slovakia [10, 13, 14] but challenged by the Danish group reporting that the incidence of ETV6-RUNX1 is the same as the incidence of ETV6-RUNX1 related ALL [15]. The purported coincidence of overt ALL and related PFG suggested an effective approach for early ALL diagnostics by screening UCB of newborns.…”
Section: Introductionmentioning
confidence: 93%
“…The incidence of pediatric ALL peaks at 3–5 years of age, but in many cases the initiating events occur in utero, with greater than 70% of patients having detectable leukemia‐initiating cells (LICs) at birth . The size of the early preleukemic cell population has been reported to correlate with time to diagnosis in some studies , so the quantity of preleukemic cells, rather than simply their presence, may be a relevant marker for ALL risk .…”
Section: Introductionmentioning
confidence: 99%
“…We have not estimated the sensitivity of monoplex RT-PCRs which is expected to reach at least the sensitivity of multiplex RT-PCR. The sensitivity of RT qPCR is significantly higher, reaching in our laboratory maximum level of ~ 1-3 x 10 -5 [16] which may be considered as too high providing no benefit for primary diagnostics. Extremely high sensitivity of RT qPCR can be utilized for monitoring of minimal residual disease during leukemic patient's treatment.…”
Section: Discussionmentioning
confidence: 71%
“…The sensitivity of multiplex RT-PCR we used in this study was estimated to be approx. 5 x 10 -3 using standard plasmids with cloned gene fusions in pCR II TOPO vector as template [16]. The real sensitivity of our multiplex RT-PCR might be slightly lower because our sensitivity test assay did not take into consideration the efficiency of cDNA synthesis which is integral part of the RT-PCR method.…”
Section: Discussionmentioning
confidence: 99%